ENGLISH TEACHERS’ BELIEFS AND THEIR FACTORS (Journal of Research and Educational Research Evaluation, 2012)
Penelitian ini bertujuan mengkaji faktor-faktor yang  mempengaruhi beliefs guru. Penelitian etnografi ini  melibatkan lima orang guru SMA di Kota Magelang. Data dikumpulkan dari silabus, rencana pembelajaran dan lembar kerja, rekaman kustioner, wawancara terstruktur, observasi kelas, dan stimulated recall. Sedangkan analisis data mengunakan model Spreadly (1980). Hasil analisis data menunjukkan pengalaman dan ekperimen dalam  pembelajaaran bahasa yang dilakukan oleh guru berperan dalam pembentukan belief. Pendidikan pada lembaga pendidikan tenaga kependidikan merupakan tahap awal dalam perkembangan professionalisme guru. Hal itu memberi perspektif baru dan membekali pengetahuan dan ketrampilanmengajar. Berkaitan dengan in-service program yang diikuti, hal itu tidak berpengaruh secara signifikan sebagai sumber pembentukan beliefs pada guru.The study explores the factors that affect teachers’ beliefs. This ethnography study involved 5 SMA teachers in Magelang Municipality. The data collected from syllabuses, lesson plans,and worksheets, recording, questionnaire, structured interviews, classroom observations, and stimulated recall. While data analysis used model of Spreadly (1980). Data analysis shows teachers’ prior experiences as well as experimentation of language learning appear to play asignificant role inthe formation of beliefs. Pre-service  education often provides the first step in the professional development of teachers. It exposes pre-service teachers to new perspectives as well as prepares them in knowledge and skills.In line with in-service program the teachers in this study did not identify it as being a significant source of influence for them.